Long-term survival benefit after allogeneic hematopoietic cell transplantation for chronic myelomonocytic leukemia - Gagelmann, Nico; Bogdanov, Rashit; Stoelzel, Friedrich; Rautenberg, Christina; Panagiota, Victoria; Becker, Heiko; Radujković, Aleksandar; Luft, Thomas; Christopeit, Maximilian Erich Joachim; Finke, Jürgen; Platzbecker, Uwe; Ditschkowski, Markus; et al. (Transplantation and cellular therapy, 2021)
The critical question in the management of chronic myelomonocytic leukemia (CMML) is which patients may benefit from allogeneic hematopoietic cell transplantation (allo-HCT). Using ad hoc statistical analysis, we designed a multicenter retrospective study to determine outcomes in 261 patients age <= 70 years at diagnosis who underwent allo-HCT (n = 119) compared with those who did not (n = 142) according to the current CMML-specific prognostic scoring system (CPSS). Categorizing patients as lower risk (CPSS low/intermediate-1) or higher risk (intermediate-2/high) showed significantly improved outcomes after transplantation in higher-risk patients, with a 37% reduced hazard for death. However, although higher CPSS was associated with worse outcomes in the non-transplantation group, the score was of limited utility for post-transplantation risk stratification. This study may provide further support for the potentially beneficial role of allo-HCT in terms of long-term survival in higher-risk patients but also underscores the need for transplantation-specific risk assessment. Recognizing limitations of retrospective comparisons, larger and prospective comparisons are needed to further refine the indication for allo-HCT and thus counseling of patients with CMML. (C) 2020 The American Society for Transplantation and Cellular Therapy. Published by Elsevier Inc. All rights reserved.